Non-coding RNAs in cardiovascular diseases: diagnostic and therapeutic perspectives - Poller, Wolfgang; Haas, Jan; Meder, Benjamin (European heart journal, 2018)
Abstract. Recent research has demonstrated that the non-coding genome plays a key role in genetic programming and gene regulation during development as well as